Optimization of Genetic Algorithm for Implementation Designing and Modeling in Academic Scheduling - Tri Suratno; Niken Rarasati; Gusmanely Z` (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
This research was investigated using the Genetic Algebra Method for scheduling lectures and practicums. Genetic algorithms are used to solve problems that are modeled according to evolutionary principles in biological sciences. The application of the Genetic Algebraic Method for Scheduling Lectures and Practices is expected to be further developed into a computerized system that can replace the manual lecture scheduling and practicum methods so that it can produce a more accurate schedule with existing rules in a shorter time. The results of the use of the genetic algorithm method are obtained from the results of the data which are fixed scheduling lecture data and can be recommended for lectures according to the lecture schedule obtained from the results of generating genetic algorithms.